La manualistica liceale storica e la questione ambientale: un’occasione mancata? - Elia, Domenico Francesco Antonio (Studi sulla Formazione/Open Journal of Education, 2022)
This contribution adopts the definition of «environmental artefact» (Macry 1995, p. 66) to analyze the pages of upper school textbooks of history dealing with environmental issues. The history school syllabuses used in these institutes include some study of the relationships between climate and economy. However, they seem less inclined to investigate those «local processes of alteration and contamination» (Bevilacqua 2011, p. 53) that have put the socio-economic order of our planet in crisis. Including these historical processes in school textbooks would promote more environmental sensitivity in the new generations.